Developing ICT-Based Learning Media Using Powtoon for Teaching Descriptive Text - Sintayani, Ni Luh; Padmadewi, Ni Nyoman; Budiarta, Luh Gd Rahayu (STKIP AGAMA HINDU SINGARAJA, 2022)
The purpose of this study was to construct a PowToon animation video as an English teacher and learning medium for seventh-grade students in junior high school, specifically to teach writing descriptive text that is more engaging. The researcher used Design and Development method to develop the product. ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method was selected as the design and development paradigm. The teacher and seventh-grade students of SMP Negeri 2 Sawan were the focus of this study. For data collection, the researcher conducted interviews, syllabus analysis, questionnaire distribution, and expert judgment rubric. Regarding descriptive text material, the PowToon animation video had an animal, a person, and a thing. The video was classified as good media based on the expert judgments rubric for material and media components. In addition, it increased students' enthusiasm and interest in learning English, particularly in improving their writing skills.